Hedge Funds Portfolio Constructions: Qualitative and Quantitative Insights - Frankowski, Jacek (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
Following the significant growth of hedge funds industry in recent years and increasing interest of institutional investors in the field, there has been observed a tendency to form various, client-tailored investment vehicles, such as funds-of-funds to suit investors’ demand. Assets allocation among alternative investment vehicles with such a different risk profiles employs, besides strictly quantitative rules, also subjective, qualitative factors derived from due diligence process. The research investigates the subject of hedge funds portfolio construction process which has become a vivid decision making task where well known portfolio optimisation methods, such as Markowitz and Sharpe, do not apply directly. Acquisition and systemization of domain knowledge is pursued in the context of decision support within portfolio construction and compliance monitoring.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 25, s. 75-84